Anesthesia Management for Pediatrics with Congenital Heart Diseases Who Undergo Cardiac Catheterization in China - Chun-Mei Xie; Yun-Tai Yao (Journal of Interventional Cardiology)
Objectives. The goal of this study was to summarize anesthesia management for pediatrics with congenital heart diseases who undergo cardiac catheterization procedure in China. Methods. The relevant articles were identified through computerized searches in the CNKI, Wanfang, VIP, and PubMed databases through May 2020, using different combinations of keywords: “congenital heart diseases,” “pediatric,” “children,” “anesthesia,” “cardiac catheterization,” “interventional therapy,” “interventional treatment,” “interventional examination,” and “computed tomography.” Results. The database searches identified 48 potentially qualified articles, of which 25 (9,738 patients in total) were determined to be eligible and included. The authors collect data from the article information. Anesthesia methods included endotracheal intubation or laryngeal mask ventilation general anesthesia, monitored anesthesia care, and combined with sacral canal block. Anesthesia-related complications occurred in 7.41% of the patients and included dysphoria, respiratory depression, nausea, vomiting, cough, increased respiratory secretion, and airway obstruction. The incidence of procedure-related complications was 12.14%, of which the most common were arrhythmia and hypotension. Conclusions. For pediatric patients with congenital heart diseases who undergo cardiac catheterization procedures in China, arrhythmia and hypotension are the most common procedure-related complications. Monitored anesthesia care is the commonly used anesthesia methods, and dysphoria, cough, nausea, vomiting, and respiratory depression are frequent complications associated with anesthesia.